El interés procesal - Juan Carlos Riofrío Martínez-Villalba (Ius Humani. Jornal do direito, 2008)
This paper aims to clarify the concept of procedural interest and systematize the different kinds of interest required by the laws of our legal system (legitimate interest, direct, serious, diffuse, collective, mutual, general public, etc.), in order to provide to the lawyer determining the existence thereof.